Amygdala-prefrontal connectivity during appraisal of symptom-related stimuli in obsessive-compulsive disorder - Paul, Sandra; Beucke, Jan Carl; Kaufmann, Christian; Mersov, Anna; Heinzel, Stephan; Kathmann, Norbert; Simon, Daniela (Psychological medicine, 2019)
BackgroundCognitive models of obsessive-compulsive disorder (OCD) posit dysfunctional appraisal of disorder-relevant stimuli in patients, suggesting disturbances in the processes relying on amygdala-prefrontal connectivity. Recent neuroanatomical models add to the traditional view of dysfunction in corticostriatal circuits by proposing alterations in an affective circuit including amygdala-prefrontal connections. However, abnormalities in amygdala-prefrontal coupling during symptom provocation, and particularly during conditions that require stimulus appraisal, remain to be demonstrated directly.MethodsAmygdala-prefrontal connectivity was examined in unmedicated OCD patients during appraisal (v. distraction) of symptom-provoking stimuli compared with an emotional control condition. Subsequent analyses tested whether hypothesized connectivity alterations could be also identified during passive viewing and the resting state in two independent samples.ResultsDuring symptom provocation, reductions in positive coupling between amygdala and orbitofrontal cortex were observed in OCD patients relative to healthy control participants during appraisal and passive viewing of OCD-relevant stimuli, whereas abnormally high amygdala-ventromedial prefrontal cortex coupling was found when appraisal was distracted by a secondary task. In contrast, there were no group differences in amygdala connectivity at rest.ConclusionsOur finding of abnormal amygdala-prefrontal connectivity during appraisal of symptom-related (relative to generally aversive) stimuli is consistent with the involvement of affective circuits in the functional neuroanatomy of OCD. Aberrant connectivity can be assumed to impact stimulus appraisal and emotion regulation, but might also relate to fear extinction deficits, which have recently been described in OCD. Taken together, we propose to integrate abnormalities in amygdala-prefrontal coupling in affective models of OCD.
Published online by Cambridge University Press: 06 April 2018
Gesehen am 09.09.2020